2005
DOI: 10.1158/0008-5472.can-04-2983
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Endogenous Retrovirus K in Melanomas and Melanoma Cell Lines

Abstract: The human endogenous retrovirus K family (HERV-K) comprises 30 to 50 closely related proviruses, most of which are defective. In contrast to all other human endogenous retroviruses, some HERV-K proviruses have maintained open reading frames for all viral proteins. In addition to the structural proteins Gag and Env and the reverse transcriptase, two regulatory proteins (Rec and Np9) have been described. Malignant melanoma has the highest mortality among skin cancers and is particularly aggressive. To study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
252
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(260 citation statements)
references
References 30 publications
5
252
0
3
Order By: Relevance
“…Most of the HERVs are defective; however, some, such as HERV-K, have retained open reading frames for all viral proteins (Löwer et al, 1996) or at least for the functional envelope protein ([de Parseval et al, 2003] and [Dewannieux et al, 2005]). Different genes of HERV-K such as the gag gene, encoding for the core proteins, the pol gene encoding for the reverse transcriptase converting the genomic RNA into proviral DNA, and the env gene, encoding the envelope proteins involved in receptor recognition and membrane fusion, as well as the accessory proteins Rec and Np9 (Löwer et al, 1993), are expressed in germ cell tumours ( [Löwer et al, 1996] and [Götzinger et al, 1996]) and melanomas ( [Muster et al, 2003], [Büscher et al, 2005] and [Büscher et al, 2006]). There are several indications that Rec and Np9 may be involved in tumour induction ( [Boese et al, 2000], [Armbruester et al, 2002] and [Galli et al, 2005]).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the HERVs are defective; however, some, such as HERV-K, have retained open reading frames for all viral proteins (Löwer et al, 1996) or at least for the functional envelope protein ([de Parseval et al, 2003] and [Dewannieux et al, 2005]). Different genes of HERV-K such as the gag gene, encoding for the core proteins, the pol gene encoding for the reverse transcriptase converting the genomic RNA into proviral DNA, and the env gene, encoding the envelope proteins involved in receptor recognition and membrane fusion, as well as the accessory proteins Rec and Np9 (Löwer et al, 1993), are expressed in germ cell tumours ( [Löwer et al, 1996] and [Götzinger et al, 1996]) and melanomas ( [Muster et al, 2003], [Büscher et al, 2005] and [Büscher et al, 2006]). There are several indications that Rec and Np9 may be involved in tumour induction ( [Boese et al, 2000], [Armbruester et al, 2002] and [Galli et al, 2005]).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the possibility that, depending on the dose employed, PG can use different cellular receptors which are present on melanoma cells, i.e. various growth factor receptors, which mediate different signal transduction pathways, cannot be ruled out [10].Finally, it is worth mentioning that melanomas are, in addition to teratocarcinomas and human breast cancer, the third tumor type with enhanced expression of HERV-K [39], and A-375 melanoma cells have been found to be positive for HERV-K encoded proteins in different studies [37,39,40]. Interestingly, a study performed almost thirty years ago by Ono and coll.…”
Section: Discussionmentioning
confidence: 99%
“…Futhermore, it has been shown that several human endogenous retroviruses are transcriptionally active in some tumors, such as germline tumors and melanoma, with evidence in some cases for expression of virus-like particles. [26][27][28] Another important outcome of the present study concerns the molecular characterization of the NeRV virus expressed by Neuro-2a cells, which provides hints to ''reconstruct'' a molecular history, leading to the generation of the fully transformed, invading Neuro-2a tumor. Indeed, the complete sequencing of the viral NeRV RNA shows that this element has most probably been generated by a recombination event, a process which is a rather common feature for infectious retroviruses.…”
Section: Discussionmentioning
confidence: 99%